2012
DOI: 10.3340/jkns.2012.51.4.215
|View full text |Cite
|
Sign up to set email alerts
|

Our Experience with Surgically Treated Epidural Hematomas in Children

Abstract: ObjectiveTraumatic epidural hematomas (EDHs) in children are a relatively unusual occurrence. The cause and outcome vary depending on period and region of study. The aims of this analysis were to review the cause and outcome of pediatric EDHs nowadays and to discuss outcome-related variables in a large consecutive series of surgically treated EDH in children.MethodsThis is a retrospective review of 29 patients with surgically treated EDHs between Jan 2000 and February 2010. Patients' medical records, computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 12 publications
3
23
0
3
Order By: Relevance
“…This finding can be seen both in studies in the United States 29 and in other Brazilian studies 2,30 . The study by Conde et al 30 showed that fatigue in patients with PPS is not related to time of day (morning or evening) but with the type of activity.…”
Section: Discussionsupporting
confidence: 56%
“…This finding can be seen both in studies in the United States 29 and in other Brazilian studies 2,30 . The study by Conde et al 30 showed that fatigue in patients with PPS is not related to time of day (morning or evening) but with the type of activity.…”
Section: Discussionsupporting
confidence: 56%
“…The incidence of EDH has been reported between 1% and 6% of hospitalized patients following a traumatic brain injury. [581424] Children with EDH are less likely to lose consciousness from the traumatic event and require immediate surgery less frequently. They also show a lower incidence of intradural hematomas compared with adults.…”
Section: Introductionmentioning
confidence: 99%
“…[812] The incidence of associated skull base fractures is lower, the course is more insidious and the signs, symptoms, and outcomes are different from adults. [81214] These make them difficult to diagnose and manage. The reported mortality rates are between 0% and 12%.…”
Section: Introductionmentioning
confidence: 99%
“…Several pediatric case series concerning various strategies of treatment of EDH have been published so far [13], our series, however, seems to be the largest in the past 10 years. Presented data reveal an increasing trend in the diagnostics and surgical treatment of EDH in children.…”
Section: Discussionmentioning
confidence: 83%